School‐wide implementation of positive behavioral interventions and supports in an alternative school setting: A case study. Issue 6 (18th June 2019) - Griffiths, Amy‐Jane; Diamond, Elena Lilles; Alsip, James; Furlong, Michael; Morrison, Gale; Do, Bich
Abstract: Aims: The purpose of this 1‐year case study was to identify how School‐Wide Positive Behavioral Interventions and Supports (SW‐PBIS) can be adapted to meet the needs of students in alternative schools and to evaluate the early impact of SW‐PBIS on discipline outcomes. Methods: Suggestions for adaptations are provided at each stage of the intervention process with a focus on buy‐in, training, data collection, and resource allocation. Results: Data from this case study included information about key components of the implementation process as well as initial outcomes. Process data revealed the importance of stakeholder buy‐in, training opportunities, and potential adaptations to the framework. Outcome data from the first year of implementation indicated that the number of incident reports did not significantly differ from the baseline; however, there was a reduction in defiance‐related behaviors and an increase in on‐task behaviors. Conclusion: This study contributes to the determination of the efficacy of SW‐PBIS in a historically more punitive environment. Given the initial positive response and lessons learned, it is believed that, with the support of additional Tier 2 and Tier 3 interventions, SW‐PBIS may be an appropriate framework to support students in alternative schools.